2016
DOI: 10.1074/jbc.m115.712091
|View full text |Cite
|
Sign up to set email alerts
|

Translation Control of Swarming Proficiency in Bacillus subtilis by 5-Amino-pentanolylated Elongation Factor P

Abstract: Elongation factor P (EF-P) accelerates diprolyl synthesis and requires a posttranslational modification to maintain proteostasis. Two phylogenetically distinct EF-P modification pathways have been described and are encoded in the majority of Gramnegative bacteria, but neither is present in Gram-positive bacteria. Prior work suggested that the EF-P-encoding gene (efp) primarily supports Bacillus subtilis swarming differentiation, whereas EF-P in Gram-negative bacteria has a more global housekeeping role, prompt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 35 publications
5
62
0
Order By: Relevance
“…EF‐P proteins are thought to be activated by post‐translational modification and B. subtilis EF‐P is post‐translationally modified by a 5‐aminopentanol group attached to lysine 32 (Rajkovic et al, ). B. subtilis EF‐P resolved as two bands in semi‐native gel electrophoresis and Western blot analysis, and we hypothesized that the two bands could represent different states of EF‐P modification and/or activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EF‐P proteins are thought to be activated by post‐translational modification and B. subtilis EF‐P is post‐translationally modified by a 5‐aminopentanol group attached to lysine 32 (Rajkovic et al, ). B. subtilis EF‐P resolved as two bands in semi‐native gel electrophoresis and Western blot analysis, and we hypothesized that the two bands could represent different states of EF‐P modification and/or activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In nearly all systems studied to date, depletion of EF‐P is either lethal or results in severe growth limitation, presumably due to the impaired ability to translate target sequences in essential genes (Schnier et al, ; Patel et al, ; Balibar et al, ; Yanagisawa et al, ). The one exception thus far is the Gram positive firmicute bacterium Bacillus subtilis where EF‐P is not required for growth and is instead specifically required for swarming motility, a flagellar‐mediated multicellular behavior in which cells rapidly move across a semi‐solid surface (Kearns et al, ; Rajkovic et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the proline-specific translation elongation factors EF-P and IF-5A is usually achieved by post-translational elongations of the ε-amino group of a conserved lysine. [18][19][20][21][49][50] The resultant noncanonical amino acidsβ-lysinyl-hydroxylysine, hypusine and 5-amino-pentanolyl-lysine -appear to be chemically and structurally analogous. We recently showed that in a subset of bacteria a so far unappreciated form of post-translational modification plays an important role in the activation of EF-P.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , a specialized elongation factor (EF-P in bacteria and eIF5A in eukaryotes) promotes efficient translation of Pro codons [6971]. Enhancement of Pro translation by EF-P or eIF5A requires diverse post-translational modifications, including β-lysylation in E. coli and Salmonella [72, 73], rhamnosylation in Pseudomonas auruginosa [74], lysine modification with 5-aminopentanol group in Bacillus [75], and hypusine in yeast [71]. …”
Section: Discrimination Of Amino Acids By the Ribosomementioning
confidence: 99%